Mengembangkan Keterampilan Motorik Halus Menggunakan Model Project Based Learning dari Bahan Alam pada Anak Kelompok A - Gina Aulia; Aslamiah Aslamiah (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
This research was motivated by the problem of children's low ability to coordinate hand and vision movements, which directly impacts their activities and fine motor skills. This study aims to describe the activities of teachers and children and analyze the development of fine motor skills in group A students at Hidayatullah Kindergarten Barito Kuala. This study used a Classroom Action Research (CAR) approach with a qualitative design and was conducted over four meetings. The results showed a significant increase in teacher activities and the development of children's fine motor skills. Teacher activities that initially received a score of 18 in the fairly good category increased to a score of 32 in the very good category at the fourth meeting. Meanwhile, at the beginning of the intervention, only 7% of children were in the Very Well Developed (BSB) category. After the first intervention, the percentage of children in the BSB category increased to 27% or five children. A more significant increase occurred at the fourth meeting, with 14 children or 82% falling into the BSB category. The intervention used a project-based learning model combined with a demonstration method in stringing activities using natural materials. Based on the results obtained, it can be concluded that this model is effective in improving fine motor skills in early childhood. This combination of approaches encourages active child engagement and provides meaningful and contextual learning experiences, contributing to optimal fine motor development.